Conformation‐Tuning Effect of Asymmetric Small Molecule Acceptors on Molecular Packing, Interaction, and Photovoltaic Performance. Issue 30 (29th June 2020) - Luo, Zhenghui; Ma, Ruijie; Xiao, Yiqun; Liu, Tao; Sun, Huiliang; Su, Mengyao; Guo, Qing; Li, Guanghao; Gao, Wei; Chen, Yuzhong; Zou, Yang; Guo, Xugang; et al.
Abstract: Understanding the conformation effect on molecular packing, miscibility, and photovoltaic performance is important to open a new avenue for small‐molecule acceptor (SMA) design. Herein, two novel acceptor–(donor‐acceptor1‐donor)–acceptor (A‐DA1D‐A)‐type asymmetric SMAs are developed, namely C‐shaped BDTP‐4F and S‐shaped BTDTP‐4F . The BDTP‐4F ‐based polymer solar cells (PSCs) with PM6 as donor, yields a power conversion efficiency (PCE) of 15.24%, significantly higher than that of the BTDTP‐4F ‐based device (13.12%). The better PCE for BDTP‐4F ‐based device is mainly attributed to more balanced charge transport, weaker bimolecular recombination, and more favorable morphology. Additionally, two traditional A‐D‐A‐type SMAs (IDTP‐4F and IDTTP‐4F ) are also synthesized to investigate the conformation effect on morphology and device performance. Different from the device result above, here, IDTP‐4F with S‐shape conformation outperforms than IDTTP‐4F with C‐shape conformation. Importantly, it is found that for these two different types of SMA, the better performing binary blend has similar morphological characteristics. Specifically, both PM6:BDTP‐4F and PM6:IDTP‐4F blend exhibit perfect nanofibril network structure with proper domain size, obvious face‐on orientation and enhance donor‐acceptor interactions, thereby better device performance. This work indicates tuning molecular conformation plays pivotal role in morphology and device effciciency, shining a light on the molecular design of the SMAs. Abstract : In this work, two novel A‐DA1 D‐A‐type asymmetric SMAs are developed, namely C‐shaped BDTP‐4F and S‐shaped BTDTP‐4F . As a result, C‐shape BDTP‐4F‐based device yields a higher PCE (15.24%) than that of S‐shape BTDTP‐4F‐based device (13.12%), while for traditional A‐D‐A type SMAs, IDTP‐4F with S‐shape conformation is better than that of C‐shape IDTTP‐4F.